ADAPTIVE SMART LEARNING MODEL: INOVASI PEMBELAJARAN DIGITAL BERBASIS KECERDASAN TEKNOLOGI DI MADRASAH IBTIDAIYAH - Bali, Muhammad Mushfi El Iq; Wulandari, Ika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Study This aim implementing the Adaptive Smart Learning Model through the Quizizz platform to increase achievements cognitive, active, and motivational students in the eye Science lessons at MI Nurul Qodir. Focus mainly is evaluate effectiveness technology intelligent in transform material abstract "Seeing Because of Light" becomes experience interactive and responsive digital learning. Research methods used is qualitative descriptive with subject teacher and 9 students selected class V through purposive sampling. Data were collected through observation participatory, interview in-depth, and documentation score students. Data analysis was carried out in a way interactive through reduction, presentation, and withdrawal conclusion with technique triangulation For ensure validity findings. Research result show transition from Teacher-centered learning (35% participation) becomes a responsive, adaptive model. The Real-Time Dashboard and Instant Feedback features are proven. effective delete misconceptions, marked with surge average value from 57.2 to 87.2 and completeness classical 100%. Although constrained internet connection, this model success increase total participation and change perception Study become competitive digital adventure.